The effect of supervision, work motivation, and competence on employee work productivity - Reza Hanindya Irfansah; Sri Hartono; Umi Farida (Privietlab, 2026)
Employee work productivity at the Magetan Regency Cooperative and Small and Medium Enterprises (SME) Agency still faces several challenges, particularly in terms of service effectiveness, equitable distribution of SME support, and speed of administrative processing. This study aimed to analyze the effect of supervision, work motivation, and competence on employee work productivity at the Magetan Regency Cooperative and SME Office. A quantitative approach was used, employing a survey method through the distribution of questionnaires to all 36 employees using a saturation sampling technique. The data were analyzed using multiple linear regression and simultaneous analysis between variables. The results show that supervision, work motivation, and competence have a positive and significant effect on employee work productivity, both partially and simultaneously. This suggests that improving the quality of supervision, fostering work motivation, and developing staff competence are key factors in enhancing productivity in the workplace. This study implies that organizations must strengthen their supervision systems, boost motivation through appropriate rewards, and continuously develop employees’ competencies to support optimal organizational performance.